Delayed bowel necrosis due to inferior mesenteric artery occlusion in Stanford type A acute aortic dissection. (25th October 2022) - Kawaguchi, Yasuhiko; Fukumoto, Yuichiro; Tamaki, Mototsugu; Kitamura, Hideki
Abstract: Although inferior mesenteric artery occlusion due to acute aortic dissection sometimes occurs, it is usually not considered an important finding. Herein, we present an extremely rare case of delayed bowel ischaemia due to inferior mesenteric artery occlusion in Stanford type A acute aortic dissection that highlights the need for cardiac surgeons to be mindful of inferior mesenteric artery occlusion in patients with superior mesenteric artery dissection or vascular anomalies in the mesenteric arteries. Abstract : Organ malperfusion is a life-threatening complication of acute aortic dissection (AAD) [1].